2011
DOI: 10.1128/jvi.01406-10
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibition of Human Immunodeficiency Virus Type 1 Infection by Virus Capsid Destabilization

Abstract: Human immunodeficiency virus type 1 (HIV-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
325
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(363 citation statements)
references
References 39 publications
35
325
3
Order By: Relevance
“…As a control, we performed similar infections in the presence of PF74 ( Figure 4). As previously shown PF74 blocks HIV-1-GFP and SIV mac -GFP infection [5,6,17,24]. Interestingly, we found a parallel between the ability of BI-2 to inhibit infection by HIV-GFP and SIV mac -GFP with the ability of BI-2 to prevent the binding of CPSF6 with the HIV-1 and SIVmac cores.…”
Section: Ability Of Bi-2 To Block Infection By Different Retrovirusessupporting
confidence: 84%
See 2 more Smart Citations
“…As a control, we performed similar infections in the presence of PF74 ( Figure 4). As previously shown PF74 blocks HIV-1-GFP and SIV mac -GFP infection [5,6,17,24]. Interestingly, we found a parallel between the ability of BI-2 to inhibit infection by HIV-GFP and SIV mac -GFP with the ability of BI-2 to prevent the binding of CPSF6 with the HIV-1 and SIVmac cores.…”
Section: Ability Of Bi-2 To Block Infection By Different Retrovirusessupporting
confidence: 84%
“…Crystal structure of the drug with the N-terminal domain of capsid (CA NTD ) revealed that BI-2 binds in the site 2 pocket [1], as it has been shown for the small-molecule inhibitor PF74 [1,4,5]. Using a novel capsid stability assay, we have demonstrated that BI-2 and PF74 stabilize in vitro assembled HIV-1 capsidnucleocapsid (CA-NC) complexes [2].…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Conceivably, the CA-NTD may modulate assembly, while being more important for its structural role within the mature capsid, or its role in the early stages of infection, mediated via interactions with cellular factors such as CypA, CPSF-6, or nuclear porins. Consistent with this suggestion, although assembly inhibitors with binding sites in the CA-NTD in some cases lead to a reduction in virus production, binding of other molecules to the CA-NTD instead inhibit virus maturation (36) or act during early infection (37).…”
Section: Resultsmentioning
confidence: 64%
“…This could be well explained with the experiences faced with the experimental uncoating inhibitor PF74 and the maturation inhibitor bevirimat. The action of both these drugs can be nullified by HIV with simple mutations causing amino acid substitutions and these resistant mutants are expected to emerge rapidly if these drugs get approved for widespread use [41,73]. While comparing the length of time and amount of work required to approve new anti-retroviral molecules acting on viral components, it is almost an instantaneous process for HIV to develop resistance against the drugs.…”
Section: Novel Targets and Synthetic Molecules To Inhibit Active Retrmentioning
confidence: 99%